Resultados de la cirugía bariátrica en pacientes diabéticos con índice de masa corporal mayor a 35 Kg/m 2 - Csendes J., Attila; Rojas C., Jorge (Revista Hospital Clínico Universidad de Chile, 2012)
Obesity and diabetes mellitus II (DMII) are closely related and have high prevalence around the world as in Chile. The term “diabesity” defines the DMII as a result of physiopathologic, metabolic and inflammatory events depending of obesity. This article summarizes the results of bariatric surgery in diabetic patients with BMI > 35 kg/M 2. It makes a review of results in our hospital and compares them with International Literature. Although the bariatric surgery in diabetic patients is a field of constant investigation, the International and National literature have shown excellent results in patients with BMI > 35 kg/m 2. Therefore it is important to continue the investigations concerning these diseases in order to determine all variables that are related to the final results. Bariatric surgery is the recommended therapeutic option for adults with BMI > 35, specially, if their DMII is difficult to control with medical treatment. These diabetic patients who undergo bariatric surgery need a close follow up and clinical and metabolic support during their life. This type of patients needs an integral and multidisciplinary treatment, including the education which plays a transcendental role to get optimal results.